Kajian Model Komunikasi Humas Pemerintah Daerah: (Studi Kasus Model Komunikasi Daerah Humas Pemerintah Daerah Kabupaten Sragen pada Acara HUT Sragen Ke-278) - Anissa Yuni Muktiarsih; Rahmat Wisudawanto; Esfandani Peni Indreswari (Institut Nalanda, 2025)
This research analyzes the communication model of Sragen Regency Government Public Relations in celebrating the 278th Sragen Anniversary based on Grunig and Hunt's theory. The research objective was to identify the application of four communication models: Press Agentry, Public Information, Two-Way Asymmetrical, and Two-Way Symmetrical. Using a descriptive qualitative approach, data was collected through observation, interviews, and documentation. The results showed that the three models-Press Agentry, Public Information, and Two-Way Symmetrical-have been effectively implemented in disseminating information and building relationships with the community. However, the Two-Way Asymmetrical model is still not optimal in building research-based and persuasive communication. The implications of this research emphasize the need to improve the government's communication strategy to better understand the audience and adjust a more effective communication strategy.